The Jinx, the dolphin, and the deep sea mystery - Maranan, Ed; Aragon, Girlie. M. (Makati City The Bookmark, Inc., 2000)
"In the fishing village of Taliwas, a child with dolphin features is born. People are shocked and amused. She swims like a dolphin, and is able to communicate with the creatures of the sea. At first Sabel is welcomed as sign of luck. Then both her parents die. Later, fish start disappearing in the sea. The child gets blamed for all these misfortunes. She is called a jinx, a curse on the village, and is forced to go on exile on a small island. The children of the village set out to search for her, but they all vanish. Sabio, her dolphin friend, reveals to Sabel the mystery behind the disappearing fish and children. With the people of Taliwas, they set out to fight the evil that lurks out at sea."
"Second prize winner, short story for children, 1991 Carlos Palanca Memorial Awards for Literature."--Title page.
Keywords: Children's stories; Children's stories, English